MUI Legal Fatwa on Vaccine Halalness in COVID-19 Vaccination Socialization in Medan City, Indonesia - Khoiri, Nispul; Nasution, Adelina (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
One of the Government's strategic policies in suppressing and stopping the transmission of COVID-19 is to take the vaccination movement seriously. Even though the vaccination program has a positive aim, while people have doubt and even refuse to use vaccines because they are considered illegal and dangerous. Responding to this friction, this is where the importance of the MUI fatwa in socializing that vaccination is very urgent and allowed to be carried out. There is no serious objection to vaccination in Medan City; even most Medan Muslims claim that the MUI fatwa brings benefits. This article belongs to field research with a qualitative approach. The methodology used is an interpretive study of the sociology of law by conducting interviews and reviewing documents related to the MUI fatwa on COVID-19 vaccination. The result concluded that; the MUI fatwa in Medan City has been well received by the community and is considered necessary. Second, the effectiveness of the halal Sinovac vaccine has been tested and is of good quality and is allowed to use. There is no severe objection regarding vaccination in Medan City; even most Medan Muslims claim that the MUI fatwa brings benefits.